PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ARTICUALATE STORYLINE PADA PEMBELAJARAN IPA MATERI EKOSISTEM UNTUK SISWA KELAS V SDN KALORAN II - Rika Putri Rahayu; Bagus Amirul Mukmin; Ilmawati Fahmi Imron (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by finger painting activities. Finger painting is a painting technique that uses children's fingers to apply color to blank paper. The purpose is to see the development of children's creativity and train children's fine motor skills. The type of this research is descriptive research with a qualitative approach. The research subjects consisted of 33 students of class II-A at SDN 004 Samarinda Ulu. Data collection techniques included by observation, interviews, and documentation. The research instruments included observation sheets of learner and educator activities, interview sheets, and documentation. Data analysis techniques used include data collection, data reduction, data presentation, and conclusion drawing. The results of this study include: (1) Finger painting technique planning is carried out for 2 days by making teaching modules and preparing tools and materials, (2) The implementation of the finger painting technique was carried out for 2 days in the classroom and students showed an increase in the creativity category and experienced development in the fine motor category, (3) Evaluation of the finger painting technique is seen from the results of students' drawings and changes in the media used, namely from HVS paper to watercolor paper.